2003
DOI: 10.1021/jf026178h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic and Chemical Assessment of Radix Angelica (Danggui) in China

Abstract: The roots of Angelica sinensis (Danggui), a traditional Chinese medicine, have been used for invigorating blood circulation for over 2000 years in China. Three common species of Angelica roots are found in Asia: A. sinensis from China, A. acutiloba from Japan, and A. gigas from Korea. By using a molecular genetic approach, the 5S-rRNA spacer domains of the three species of Angelica were amplified, and their nucleotide sequences were determined. Diversity in DNA sequences among various species was found in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
165
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(174 citation statements)
references
References 13 publications
6
165
0
3
Order By: Relevance
“…mongholicus roots from Shanxi province and two-year-old A. sinensis roots from Minxian in Gansu province. These areas had been demonstrated to produce the best quality RA [11] and RAS [12], respectively. Preparation of the herb materials under optimized conditions was described previously [10].…”
Section: Plant Materials and Preparation Of Dbtmentioning
confidence: 99%
“…mongholicus roots from Shanxi province and two-year-old A. sinensis roots from Minxian in Gansu province. These areas had been demonstrated to produce the best quality RA [11] and RAS [12], respectively. Preparation of the herb materials under optimized conditions was described previously [10].…”
Section: Plant Materials and Preparation Of Dbtmentioning
confidence: 99%
“…Ferulic acid and ligustilide were usually chosen as marker compounds to assess the quality of CA and their products in literatures [4][5][6][7][8][9]. Pharmacological and clinical studies indicated that they were both bioactive compounds with reported activities to inhibit platelet aggregation, relax uterus, tracheal muscle, smooth muscle, prevent gynecological disease, treat menstrual disorders, urgent premature birth, hypertension, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Although there were some publications associated with CA fingerprints or multi-component chromatograms using HPLC, none of these involved multi-samples analysis, comparison between herbal species or identification using characteristic chemical components [4,[24][25][26][27]. In other literature reports, volatile compounds were qualitatively or quantitatively analyzed by GC-flame ionization detection (FID) or GC-MS in CA samples, however, the stability as well as reproducibility of these methods or relevant compounds were not mentioned [6,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…16,17) It was first introduced into the West in 1899 by Merck in the form of a liquid extract named "Eumenol" and was presently marketed in the United States as a dietary supplement, with numerous products being marketed worldwide. 18,19) In recent years, it was also reported that the polysaccharide extracts from A. sinensis possessed significant immunomodulatory activity. 20) However, it is not known whether A. sinensis polysaccharides have any direct antioxidant effects and more detailed work is needed on the elucidation of the sugar composition and antioxidant activities of active polysaccharides.…”
mentioning
confidence: 99%